Development of software tool for performance evaluation of mobile ad hoc networks using Taguchi method - Lee, Muhammad Hisyam (Faculty of Science, 2009)

(untitled)
A mobile ad hoc network (MANET) is a self-organizing collection of mobile wireless nodes formed dynamically without the use of any supporting infrastructures. The performance of MANETs are in°uenced very much by numerous factors that de¯ne the network environment and scenario, including routing protocols and scenario metrics, such as terrain size, node speed, network density etc. In this project, we are interested in determining the functional relationship between these in°uential factors and performance of MANET systems. The orthogonal arrays, signal-to-noise ratio, analysis of variance of Taguchi approach has been applied in this study. Using suitable experimental matrices, the signi¯cance e®ects of various factors and interactions a®ecting the MANET performances and routing protocols with respect to two performance metrics, namely, routing overhead and drop rates were determined. Results found that transmission range, terrain, routing protocol, node speed, network size, packet rates, tra±c load were signi¯cant on drop rates. Furthermore, the e®ects of network density, tra±c load, node mobility, and routing protocol were found to be signi¯cant on routing overhead, and the interactions between network size and transmission range were signi¯cant on the performance of Dynamic Source Routing (DSR) protocol. In comparing the performance of DSR and Ad Hoc On-Demand Distance Vector (AODV) using Taguchi approach, it is found that DSR generates less routing overhead compared to AODV.